DIFFICULT ASPECTS OF TOURISM DEVELOPMENT IN UZBEKISTAN - Ergasheva Yulduz Alimovna; Eralov Azamat Jomurodovich (Journals Park Publishing, 2022)
This article discusses topical aspects of tourism development in Uzbekistan. The author analyzes the problem on the basis of available scientific and historical literature, based on archeological data, archival documents and written sources, and explores the specifics of the subject.
Keywords: tourism; tourists; hotels